2019
DOI: 10.1007/s10973-019-08260-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and hydrodynamic performance of a microchannel heat sink with carbon nanotube nanofluids

Abstract: Comparison of optimized thermal and hydrodynamic performances of a circular and square microchannel heat sink cooled with carbon nanotube nanofluid, using experimentally obtained data. • Analysis of surfactant and viscosity effects on CNT nanofluid performance. • Utilization of multi-objective genetic algorithm (MOGA) to simultaneously minimize the thermal resistance and pressure drop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The forced convection heat transfer in microchannels with liquid has higher efficiency and is easier for utilization than other methods. Some scholars used various kinds of nanofluids as the heat transfer fluid in microchannels [7][8][9][10]. Thermal and hydrodynamic performance of an MCHS with carbon nanotube nanofluids was investigated by Normah et al [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forced convection heat transfer in microchannels with liquid has higher efficiency and is easier for utilization than other methods. Some scholars used various kinds of nanofluids as the heat transfer fluid in microchannels [7][8][9][10]. Thermal and hydrodynamic performance of an MCHS with carbon nanotube nanofluids was investigated by Normah et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars used various kinds of nanofluids as the heat transfer fluid in microchannels [7][8][9][10]. Thermal and hydrodynamic performance of an MCHS with carbon nanotube nanofluids was investigated by Normah et al [10]. The results showed that the nanotube nanofluid with lignin as the surfactant performed better thermally and hydrodynamically, due to lower viscosity at high carbon nanotube concentration compared to the nanotube nanofluid with sodium polycarboxylate surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…N3 is used for nanofluids obtained with sodium polycarboxylate as a surfactant. To make easier the implementation of thermophysical data of nanofluids in the numerical simulation and program [44], the following formulas of thermophysical properties of nanofluids have been adjusted on experimental data. The thermal expansion coefficient of nanofluids was calculated from the following equation [2] as:…”
Section: Thermophysical Properties Of Multi-walled Carbon Nanotube Nanofluidmentioning
confidence: 99%
“…Murshed [17] mention in the review paper that CNTs nanofluids have six-time higher thermal conductivity compared to other materials at ambient temperature. The CNTs nanofluids sufficiently investigated in the literature (see for example Xie et al [18], Sarafraz et al [19], Selimefendigil, and Öztop [20], Ghazali et al [21] and Abdeen et al [22]) but without memory and heredity effect. This is since, in mathematical studies, the traditional models with integer-order PDEs are utilized.…”
Section: Introductionmentioning
confidence: 99%